Nuclear Localization of HopA1Pss61 Is Required for Effector-Triggered Immunity - Hobin Kang; Quang-Minh Nguyen; Arya Bagus Boedi Iswanto; Jong Chan Hong; Saikat Bhattacharjee; Walter Gassmann; Sang Hee Kim (Plants, 2021)
Plant resistance proteins recognize cognate pathogen avirulence proteins (also named effectors) to implement the innate immune responses called effector-triggered immunity. Previously, we reported that hopA1 from Pseudomonas syringae pv. syringae strain 61 was identified as an avr gene for Arabidopsis thaliana. Using a forward genetic screen approach, we cloned a hopA1-specific TIR-NBS-LRR class disease resistance gene, RESISTANCE TO PSEUDOMONAS SYRINGAE6 (RPS6). Many resistance proteins indirectly recognize effectors, and RPS6 is thought to interact with HopA1Pss61 indirectly by surveillance of an effector target. However, the involved target protein is currently unknown. Here, we show RPS6 is the only R protein that recognizes HopA1Pss61 in Arabidopsis wild-type Col-0 accession. Both RPS6 and HopA1Pss61 are co-localized to the nucleus and cytoplasm. HopA1Pss61 is also distributed in plasma membrane and plasmodesmata. Interestingly, nuclear localization of HopA1Pss61 is required to induce cell death as NES-HopA1Pss61 suppresses the level of cell death in Nicotiana benthamiana. In addition, in planta expression of hopA1Pss61 led to defense responses, such as a dwarf morphology, a cell death response, inhibition of bacterial growth, and increased accumulation of defense marker proteins in transgenic Arabidopsis. Functional characterization of HopA1Pss61 and RPS6 will provide an important piece of the ETI puzzle.